Development of equivalent circuit models for non-linear resistors. - Solis, Romeo G.
The modeling of non-linear devices confront both users and developers of computer-aided design programs. This paper shows how large signal models for voltage and current controlled resistors can be developed based on the piece wise linear characteristics of the device. For both voltage controlled and current controlled non-linear resistors, two models are developed. One model is Foster like in the sense that the sub circuits are connected either in series or parallel to form the model. The other model is Cauer-like in the sense that the topology is of ladder type. Methods for developing the models are presented.